Direct growth of uniform carbon nitride layers with extended optical absorption towards efficient water-splitting photoanodes - Jiani Qin (Nature Portfolio, 2020)
Photoelectrochemical cells (PEC) can convert sunlight and water directly to a hydrogen fuel. Here a robust metal-free carbon nitride-based layer is used as an efficient photoanode for water-splitting PEC.